2017
DOI: 10.1016/j.wsj.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics resistance phenomenon and virulence ability in bacteria from water environment

Abstract: This study aims to determine the impact of five main drains as sources of antibiotics resistant bacteria in River Nile at Rosetta branch, and to generate a baseline data on their virulence ability. Out of 212 bacterial isolates, 39.2% and 60.8% were recovered from drains and Rosetta branch, respectively. Susceptibility of bacteria to different antibiotics showed multiple antibiotics resistances (MAR) for the majority of isolates. Meanwhile, sensitivity was mostly directed to ofloxacin and norfloxacin antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 36 publications
(34 reference statements)
2
24
0
1
Order By: Relevance
“…The presence of AMR in aquaculture production systems may not only pose a direct threat to human health, but could also impact production itself by lowering drug efficacy 23,32 , decreasing the animal's immune system as seen in rats 33 and selecting more virulent strains (i.e. faster growth and higher transmission rates of pathogens) 34 . Recent research has shown that antimicrobial use might not be the only factor behind selection and emergence of AMR and warmer temperatures have been associated with higher AMR rates in terrestrial bacteria, establishing a sombre prospect in light of global climate warming 35 .…”
mentioning
confidence: 99%
“…The presence of AMR in aquaculture production systems may not only pose a direct threat to human health, but could also impact production itself by lowering drug efficacy 23,32 , decreasing the animal's immune system as seen in rats 33 and selecting more virulent strains (i.e. faster growth and higher transmission rates of pathogens) 34 . Recent research has shown that antimicrobial use might not be the only factor behind selection and emergence of AMR and warmer temperatures have been associated with higher AMR rates in terrestrial bacteria, establishing a sombre prospect in light of global climate warming 35 .…”
mentioning
confidence: 99%
“…Odjajare et al [58] in Alice, Eastern Cape, South Africa, reported similar result with a mean MAR index of 0.46. A MAR index of isolates with values higher than 0.2 has also been reported in sh samples sold in informal markets in Zimbabwe [59] and River Nile in Egypt [57]. These isolates with MAR indices greater than 0.2 indicate that they are from potentially health risk niche.…”
Section: Isolation and Antimicrobial Susceptibility Testingmentioning
confidence: 64%
“…A MAR index > 0.2 indicates that isolates originate from high-risk sources of contamination [56] while MAR index > 0.4 is an indication of faecal origin contamination [51]. Antibiotics are increasingly present in wastewater and this contribute to the emergence and selection of AMR in the environment [57]. In the current study, analysis of MAR index of the P. aeruginosa strains showed that all of them had a MAR index above 0.2 with Mean MAR index of 0.42 and 0.34 of abattoir wastewater and aquatic isolates respectively (Fig.…”
Section: Isolation and Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…The increasing development of antimicrobial resistance in microorganisms has reached a critical point, threatening the gains over the years on the treatment of infectious diseases, since the discovery of penicillin in the early 1900s. The rate of resistance has become so astronomical that bacteria are developing defenses against antibiotics even as new ones are developed [5]. Unfortunately, this problem is not limited to clinical isolates alone but has extended to native isolates of aquatic environments [6].…”
Section: Introductionmentioning
confidence: 99%